2016
DOI: 10.1007/s00125-016-3942-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in beta cell function occur in prediabetes and early disease in the Lepr db mouse model of diabetes

Abstract: Aims/hypothesis Type 2 diabetes is a progressive disease that increases morbidity and the risk of premature death. Glucose dysregulation, such as elevated fasting blood glucose, is observed prior to diabetes onset. A decline in beta cell insulin secretion contributes to the later stages of diabetes, but it is not known what, if any, functional beta cell changes occur in prediabetes and early disease. Methods The Lepr db mouse (age 13-18 weeks) was used as a model of type 2 diabetes and a two-photon granule fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 41 publications
7
18
0
Order By: Relevance
“…Type 2 diabetes mellitus (T2DM) is the predominant form of diabetes and is characterized by insulin resistance and pancreatic β‐cell failure, which lead to abnormally high blood glucose levels (hyperglycaemia) . Impaired function of β‐cells, which are responsible for the production and secretion of insulin, is a critical contributing factor for the progression from prediabetes to diabetes . The loss of responding β‐cells in pancreatic islets has been found in genetically diabetic (db/db) mice .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type 2 diabetes mellitus (T2DM) is the predominant form of diabetes and is characterized by insulin resistance and pancreatic β‐cell failure, which lead to abnormally high blood glucose levels (hyperglycaemia) . Impaired function of β‐cells, which are responsible for the production and secretion of insulin, is a critical contributing factor for the progression from prediabetes to diabetes . The loss of responding β‐cells in pancreatic islets has been found in genetically diabetic (db/db) mice .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Impaired function of β-cells, which are responsible for the production and secretion of insulin, is a critical contributing factor for the progression from prediabetes to diabetes. 3,4 The loss of responding β-cells in pancreatic islets has been found in genetically diabetic (db/db) mice. 5 Although previous studies have reported that the β-cell-specific transcription factors pancreatic duodenal homeobox 1 (PDX-1) and v-Maf musculoaponeurotic fibrosarcoma oncogene family, protein A (MafA) play key roles in the maintenance of β-cell function and the production of insulin, 6,7 the precise molecular mechanisms underlying β-cell function and insulin expression remain largely unknown, thus greatly limiting the development of effective therapeutic strategies against T2DM.…”
mentioning
confidence: 99%
“…This drop is coincident with the increase in AUC of the GTT (Figure 4.1D) and demonstrates very clearly that altered beta-cell function is strongly associated with loss of glucose homeostasis. The new findings are consistent with my previous chapter (chapter 3), where animals with overt disease and compromised GTTs were studied ). The results now show that at stage 2 the beta-cells are still competent to secrete and that a high potassium stimulus can elicit insulin secretion.…”
Section: Beta-cell Function In Prediabetes and The Early Stages Of DIsupporting
confidence: 90%
“…The rarity of sequential/ mutigranular exocytosis in pancreatic beta-cells under normal condition is believed to play an important physiological role in prolonged regulation of blood glucose concentration whereby massive secretion is prevented. However, when stimulated with muscarinic agonist carbachol or glucagon like peptide 1 (GLP-1) in addition to glucose, compound exocytosis of the insulin-containing granules becomes quantitatively significant (3)(4) times increase) which suggests an important role of this type of exocytosis in essential conditions where insulin demand is very high (Kwan and Gaisano 2005;Hoppa, Jones et al 2012).…”
Section: Compound Exocytosis Of the Pancreatic Beta-cellsmentioning
confidence: 99%
See 1 more Smart Citation